Analisa Mekanisme Pasar Kalangan Pada Masyarakat Islam Melayu Di Kecamatan Gandus Palembang - Meriyati, Meriyati; Choiriyah, Choiriyah; Mulyawisdawati, Richa Angkita (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe market is a mechanism of exchange of products in the form of goods and services that are natural and have been going on since the beginning of human civilization. Islam places the market at an important position in the economy, a meeting place between sellers and buyers and transactions of goods or services, is a natural mechanism of exchange of goods and services and has been going on since the beginning of human civilization. In Islam the market is very important in the economy. The market had taken place during the time of the Messenger of Allah and Khulafaur Rashidin and became the sunatullah that had lived for centuries.Keywords: Mechanism, Market, Malay IslamÂ AbstrakPasar adalah sebuah mekanisme pertukaran produk baik berupa barang maupun jasa yang alamiah dan telah berlangsung sejak peradaban awal manusia. Islam menempatkan pasar pada kedudukan yang penting dalam perekonomian, tempat bertemunya antara penjual dan pembeli dan melakukan transaksi barang atau jasa, merupakan sebuah mekanisme pertukaran barang dan jasa yang alamiah dan telah berlangsung sejak awal peradaban manusia. Dalam Islam pasar sangatlah penting dalam perekonomian. Pasar telah terjadi pada masa Rasulullah dan Khulafaur Rasyidin dan menjadi sunatullah yang telah dijalani selama berabad-abad.Kata Kunci: Mekanisme, Pasar Kalangan, Islam Melayu